Development of composite indicators to monitor burden of disease across Member States. (13th November 2019) - Haneef, R; Gallay, A; Hilderink, H; Devleesschauwer, B; Ziese, T; Schmidt, J; Newton, J
Abstract: Background: The burden of disease (BoD) methods are not part of routine public health activities and policy development process across all Member States (MSs). The main reasons for this are varying levels of knowledge, experience, and capability to apply and use BoD methods. Therefore, MSs need support, guidance and training to adopt and integrate BoD approaches in their public health systems. In this context, two workshops have been organised by InfAct. The main objectives of the workshops are to raise awareness, share knowledge and experience, and to provide mutual support to to integrate BoD indicators in the public health policies across Europe. Methods: The workshops were about the BoD concept and methodologies, and the use of BoD data in public health policy. These workshops were supported by technical presentations describing methods and the use of BoD data in health policy with various case studies, followed by expert exchange with facilitated discussions and group work. The case studies included national BoD studies from Belgium, Germany, Netherland, and Scotland. Results: Two workshops were held at Santé Publique France, and attended by 16 BoD experts and 40 participants from 25 MSs. The workshops were well received by the participants particularly with regards to the diversity of the group and the possibility to share knowledge and experience from various perspectives. Three areas of action were highlighted: 1. the need for methodological trainings to strengthen skills in interpreting and calculating BoD estimates; 2. the encouragement of more collaborations across MSs to share or exchange good practices on BoD; and 3. the importance of the implications of BoD data to guide policies across MSs. Conclusions: The workshops highlighted the need for capacity building activities to implement BoD approaches across MSs in routine public health activities and to use BoD data to guide health policy. More collaborations among MSs on BoD activities are needed in the future.